A Note on Integral Inequalities on Time Scales Associated with Ostrowski's Type. (27th December 2019) - Fatima Tahir, Saeeda; Mushtaq, Muhammad; Muddassar, Muhammad
Abstract : Inequalities become a hot topic for researcher due to its wide applications in means and sum, numerical integration, quantum calculus. Different generalizations and refinements are made by researchers. Here, in this article, we give another generalization of integral inequalities and harmonizing them on time scale T from R .